2016
DOI: 10.1634/theoncologist.2015-0516
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Eventual Publication of Clinical Trial Abstracts Submitted to a Large Annual Oncology Meeting

Abstract: Background. Despite the ethical imperative to publish clinical trials when human subjects are involved, such data frequently remain unpublished. The objectives were to tabulate the rate and ascertain factors associated with eventual publication of clinical trial results reported as abstracts in the Proceedings of the American Society of Clinical Oncology (American Society of Clinical Oncology). Materials and Methods. Abstracts describing clinical trials for patients with breast, lung, colorectal, ovarian, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 46 publications
2
42
0
Order By: Relevance
“…Prior studies have correlated larger patient enrollment with likelihood of publication,(25,34–36) which is similar to our data demonstrating the importance of research biopsy number and reporting. Similar to our finding with research biopsy reporting, prior studies have demonstrated that industry funding negatively impacts clinical trial publication.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Prior studies have correlated larger patient enrollment with likelihood of publication,(25,34–36) which is similar to our data demonstrating the importance of research biopsy number and reporting. Similar to our finding with research biopsy reporting, prior studies have demonstrated that industry funding negatively impacts clinical trial publication.…”
Section: Discussionsupporting
confidence: 89%
“…(2125) In particular, recent studies have shown that a substantial proportion of clinical trials have suboptimal reporting of harm, and severe toxicity. (26,27) This single center study evaluating the rate of reporting of research biopsies in clinical trials has produced findings demonstrating that, similar to clinical trial underreporting, the absence of research biopsy reporting represents a major limitation to the transparency of clinical research.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the publication percentage of the phase 3 trials (mainly RCTs) in our cohort (73%) was higher compared to previous cohorts investigating RCTs (overall, 54% published) [16,37]. Other recent research also supports that publication of phase 3 trials has been improved [17]. So, the regularly mentioned number of 50% non-publication [38] probably needs to be updated with regard to the phase 3 trials.…”
Section: Discussionmentioning
confidence: 61%
“…The waste and bias implicated in clinical research caused by non-publication over the past years [3,6,7,8,9,10,11,12,13,14,15,16,17,18] has strengthened the view of several organizations and governments that all clinical trials must be published [19,20,21,22,23]. Previous studies specifically focused on publication of randomized controlled trials (RCTs) [24], covered only trials within one medical specialty [25], examined a limited selection of determinants, or used incomplete trial cohorts depending on public registrations [26,27] or interview response rates [10].…”
Section: Introductionmentioning
confidence: 99%
“…Because of multiple rejections and prolonged review process involved with journal publications, investigators instead prefer a less intense, non-peer-reviewed process and report their results as congress publications, such as abstracts, oral presentations, or posters. 30 These delays have ensued in selective reporting, outcome reporting, and publication biases. Selective reporting has been a norm for the past few decades; however, the trend seems to have changed since the introduction of FDAAA act.…”
Section: Article In Pressmentioning
confidence: 99%